ESI-MSn study on the fragmentation of protonated cyclic-dipeptides. Issue 3 (2009) - Guo Guo, Yan-Chun Yan-Chun; Cao Cao, Shu-Xia Shu-Xia; Zong Zong, Xiang-Kun Xiang-Kun; Liao Liao, Xin-Cheng Xin-Cheng; Zhao Zhao, Yu-Fen Yu-Fen
Abstract : Cyclic dipeptides are relatively simple compounds that can exhibit a great variety of important biological activities. The fragmentation pathways of protonated cyclic dipeptides have been studied by electrospray ionization multistage mass spectrometry (ESI-MS n ). The mass spectra studies of the cyclic dipeptides showed that the cyclic dipeptides with the similar substituents, the side chains of amino acid residues at the diketopiperazine ring, followed the same fragmentation pathway. In the fragmentation spectra of protonated cyclic dipeptides, some characteristic fragment ions were observed and could be used to distinguish the cyclic dipeptides. The hydrogen/deuterium (H/D) exchange experiment and the high-resolution mass spectrometry (Q-TOF) were used to verify and rationalize the proposed fragmentation pathways. These observations may have some potential applications in the structural elucidation and interpretation of the mass spectra of homologous compounds.